Simultaneous biosorption and bioethanol production from lead-contaminated media by Mucor indicus - Saman Samadi; Keikhosro Karimi; Sanaz Behnam (Biofuel Research Journal, 2017)
Mucor indicus with different morphologies was used for ethanol production and Pb2+ biosorption. With increasing Pb2+ concentration in the cultivation medium, the fungus morphology changed from purely filamentous to mostly filamentous and the biosorption capacity was increased. The maximum adsorption capacity predicted by Langmuir model was 118 mg/g for purely filamentous form. All morphologies were also cultivated in the presence of high Pb2+ concentration (300 mg/L) in consecutive stages. After the first stage of cultivation, the live biomass was separated and cultivated in a new medium similar to the first stage and cultivation was performed within five stages. All morphologies of M. indicus were able to grow and produce ethanol in the presence of lead at all stages but with lower yields than those cultivated in the absence of lead. The highest ethanol yields of 0.46 and 0.35 g ethanol per g consumed glucose were obtained by mostly filamentous morphology at the first and the last stages, respectively. The presence of lead decreased the glucose consumption rate of all morphologies and the yeast-like morphology consumed glucose within a shorter time than the other morphologies. Different morphologies were able to adsorb lead ions considerably (97–99%) within the five consecutive stages.